Reducing the bias of probing depth and attachment level estimates using random partial-mouth recording - Beck JD, Caplan DJ, Preisser JS, Moss K. (Blackwell Synergy, 2005)
To evaluate the bias and precision of probing depth (PD) and clinical attachment level (CAL) estimates of random and fixed partial examination methods compared with full-mouth examinations.